Red: the color of Peru - Beltrán-Suito, Rodrigo (2021)
The red color is characteristic of the symbols and emblems of Peru. It is not only present in the national flag, but is also characteristic of its national bird (Rupicola peruviana) and flower (Cantua buxifolia). Their color is due to the structural characteristics of organic substances belonging to the family of carotenoids and flavonoids. Apart from their use as colorants and pigments, these compounds also find diverse applications in pharmaceuticals and nutrition due to their antioxidant properties. This review details the specific compounds that give rise to the red color of the most representative plants and animals of Peru. The presence of unique substances not observed in other species is also highlighted.